Implementing unmanned aerial systems equipped with Sniffer4D payloads for volcanic gas detection and data analysis used for forecasting volcanic eruptions - Godfrey, Ian (2022)
A consistent volcanic monitoring program is crucial to the safety of the population and the efficiency of the nation. Costa Rica´s National Commission for Risk Prevention the CNE helps manages this responsibility. Universidad Nacional Costa Rica the National Observatory for Volcanoes OVSCORI-UNA and the Atmospheric Chemistry Laboratory LAQAT-UNA all have a strategic interest in monitoring and tracking volcanic activity. One aspect of monitoring volcanoes is tracking the active emissions being released from the craters and fumaroles. For this study the Sniffer4D gas detection payload was deployed on an UAS and flown directly into the active West Crater of the Turrialba volcano in 2022 for readings of active emissions. The Turrialba volcano is located 40 km or 25 miles East of San José the Capital city of Costa Rica where the majority of the population live. In 2017 an eruption column emerged 3,000 meters or 9,842.5 feet above the summit crater of the Turrialba volcano and dispersed ash in the capital resulting in airport closures. So monitoring the Turrialba volcano is of great importance to the country. The UAS system deployed carried the Sniffer4D which tested for Temperature, Humidity and 9 additional parameters - Sulfur Dioxide SO2 (μg/ m3), Volatile Organic Compounds VOCs (ppm), Carbon Monoxide CO (mg/m3), Carbon Dioxide CO2 (%), Ozone O3(μg/ m3), Nitrogen Dioxide NO2 (μg/ m3), O3+NO2 and Particulate Matter - PM 1.0, 2.5 & 10. Particulates – also known as atmospheric aerosol particles, atmospheric particulate matter, particulate matter (PM), or suspended particulate matter (SPM) – are microscopic particles of solid or liquid matter suspended in the air. The term aerosol commonly refers to the particulate/air mixture, as opposed to the particulate matter alone. The main objective of launching this payload into the West Crater of Turrialba was completed by Ian Godfrey in 2022.